Hyperbranched polyamide functionalized graphene oxide modified bismaleimide resin

By using hyperbranched polyamide functionalized graphene oxide (HPA-GO) modification in BMI resin, the problems of poor toughness and poor dispersion of nanoparticles are solved, and the mechanical properties of the resin are improved and the production process is simplified.

CN119463178APending Publication Date: 2025-02-18BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411513283.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Bismaleimide (BMI) resin has poor toughness and strong molecular chain rigidity in applications, and nanoparticles have poor dispersion and serious agglomeration in the resin, which affects the performance of mechanical properties. At the same time, the high viscosity and low flowability of the resin make the mixing and removal process of nanoparticles complex and costly.

Method used

Using hyperbranched polyamide functionalized graphene oxide (HPA-GO) modified BMI resin, the binding ability of GO and resin is improved by grafting HPA to the GO surface, and the solution mixing route assisted by ball mill is realized. Evenly mixing with BMI resin reduces drying and maintains dispersion.

Benefits of technology

The bending strength, modulus and glass transition temperature of the resin are significantly improved, the nanoparticle agglomeration is avoided, the mixing and removal process is simplified, the production cost is reduced, and better mechanical properties and production efficiency are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463178A_ABST
    Figure CN119463178A_ABST
Patent Text Reader

Abstract

The invention provides hyperbranched polyamide-functionalized graphene oxide (HPA-GO) modified bismaleimide (BMI) resin, and relates to the technical field of bismaleimide resin.The HPA-GO modified BMI resin is prepared from DMF (N, N-dimethylformamide) dispersion liquid of HPA-GO, diphenyl bismaleimide, deionized water and diallyl bisphenol A. The preparation method comprises the steps that the BMI resin is prepared from the following raw materials, the preparation method comprises the following steps: reacting diphenyl bismaleimide with DMF dispersion liquid of HPA-GO, washing, carrying out suction filtration, drying, adding diallyl bisphenol A, reacting, and carrying out stepped curing to obtain the HPA-GO modified BMI resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bismaleimide resins, and in particular to a hyperbranched polyamide functionalized graphene oxide modified bismaleimide resin. Background Art

[0002] Bismaleimide (BMI) resin has a higher operating temperature than traditional epoxy resin, but is less difficult to process than polyimide resin. It is an extremely important thermosetting resin in the aerospace field. However, BMI has a high cross-linking density, strong molecular chain rigidity, and poor toughness, which seriously hinders the further development and application of BMI resin. Traditional toughening methods such as adding rubber containing active groups, diamine chain extension, and forming an interpenetrating network structure usually reduce the cross-linking density of BMI resin, thereby increasing toughness, but will have a certain effect on the rigidity of BMI resin. It usually leads to a decrease in the glass transition temperature. Due to its excellent mechanical properties, graphene oxide (GO) can hinder the movement of molecular chains at high temperatures when added to BMI to increase the glass transition temperature of the resin, deflect cracks when BMI is damaged, and improve the toughness of the resin, while achieving the effect of toughening and stiffening. The large specific surface area of ​​GO enables it to play a significant role in toughening and stiffening with a small amount of addition.

[0003] R&D personnel often encounter the following problems:

[0004] 1. Nanoparticles have a very high surface energy due to their small particle size, and are prone to agglomeration in the resin. At the same time, since most of the GO surface groups are oxygen-containing groups, their compatibility with BMI resin is poor, and BMI resin has high viscosity and poor fluidity. These reasons lead to poor dispersion of GO in BMI resin, severe agglomeration, and the excellent mechanical properties cannot be fully exerted in BMI resin.

[0005] 2. GO itself has a certain degree of dispersibility in polar solvents, but after chemical modification, its dispersibility often decreases seriously and is prone to agglomeration. When using functionalized GO as a subsequent additive, in order to maintain its good dispersion state, it is often necessary to freeze-dry or heat-dry it to obtain a powder. This process is time-consuming, labor-intensive, cumbersome, complex, costly, and difficult to mass-produce.

[0006] 3. In order to add nanoparticles to the resin, the resin needs to be in a fluid state, so it is necessary to heat the molten resin or use a solution mixing method. For BMI resin, the difference between its melting point and curing temperature is not too large, and the heated molten resin is prone to gel prematurely during a long period of stirring and mixing. The solution mixing method must eventually remove the solvent after mixing evenly. The most common method is to heat and evaporate the solvent. For BMI resin, its good solvent is DMF, which has a high boiling point (153°C). The heating and evaporation temperature is high and time-consuming. The heating temperature is close to the resin gelation temperature, which is also prone to premature gelation of the resin, and DMF is often not completely removed. Premature gelation and solvent residue will cause the performance of the final cured product of the resin to deteriorate (insufficient cross-linking or defects).

[0007] 4. Currently, nanoparticles are mixed into resin mostly by mechanical stirring or ultrasonic dispersion, and the dispersion effect is not ideal.

[0008] Based on the above problems and situations, the researchers developed a hyperbranched polyamide functionalized graphene oxide (HPA-GO) modified bismaleimide (BMI) resin. Summary of the invention

[0009] The present invention provides a HPA-GO modified BMI resin to solve the problems raised in the above background technology.

[0010] In order to solve the above technical problems, the present invention discloses a HPA-GO modified BMI resin, and the preparation raw materials include the following components: DMF dispersion of HPA-GO, diphenyl bismaleimide, deionized water and diallyl bisphenol A.

[0011] Furthermore, the raw materials for preparing the HPA-GO modified BMI resin include the following components by weight: 20-50 parts of DMF dispersion of HPA-GO, 100-150 parts of diphenyl bismaleimide, 200-800 parts of deionized water and 50-225 parts of diallyl bisphenol A.

[0012] Furthermore, the raw materials for preparing the DMF dispersion of HPA-GO include the following components by weight: 10-20 parts of GO, 100-200 parts of DMF and 1-5 parts of HPA.

[0013] Furthermore, the preparation method of the DMF dispersion of HPA-GO comprises: reacting GO, DMF and HPA, washing and centrifuging to obtain HPA-GO;

[0014] Preferably, the reaction temperature of GO, DMF and HPA is 80-120° C., and the reaction time is 12-36 h.

[0015] Furthermore, the preparation method of HPA includes: adding diethylenetriamine and methyl acrylate, reacting under a nitrogen atmosphere, and adding ethylenediamine to react to obtain HPA.

[0016] Furthermore, the molar ratio of the added diethylenetriamine and methyl acrylate is 1:1.

[0017] Furthermore, the molar ratio of the added diethylenetriamine and ethylenediamine is (2-30):1.

[0018] Furthermore, the reaction temperature under nitrogen atmosphere is -10-20°C, the reaction time is 10-24h, and the reaction temperature after adding ethylenediamine is 70-140°C, and the reaction time is 5-12h.

[0019] Further, 10-50 parts of the DMF dispersion of diphenyl bismaleimide and 20-50 parts of HPA-GO are added, ultrasonically dissolved, HPA-GO is added at a weight ratio of 0.0001-0.01 to BMI resin at 50°C, stirred at a speed of 1000-8000 r / min for 1-2h, 90-100 parts of diphenyl bismaleimide are added and stirred to obtain a premixed solution, the obtained premixed solution is poured into the tank of the ball mill, and the mixture is stirred at 2 The mixture is mixed at a speed of 100-800 r / min for 2-8 hours to obtain a uniform mixed solution, the uniform mixed solution is poured into 200-800 parts of deionized water to precipitate the resin, the resin powder is washed and filtered to obtain a resin powder, and the resin powder is dried at 80-120° C.; 50-225 parts of diallyl bisphenol A are added to the resin powder at 110-140° C., and the mixture is prepolymerized for 1-2 hours with mechanical stirring at a speed of 1000-3000 r / min to obtain a prepolymer.

[0020] Furthermore, the prepolymer is subjected to a degassing treatment in a vacuum oven at 120-160° C. and then step-cured in the oven to obtain a HPA-GO modified BMI resin.

[0021] Compared with the prior art, the present invention provides a HPA-GO modified BMI resin, which has the following beneficial effects:

[0022] (1) HPA was grafted onto the surface of GO to obtain HPA-GO, thereby improving the binding ability between GO and resin.

[0023] (2) The ball-milling-assisted solution mixing route is adopted to mix and ball-mill HPA-GO and BMI resin in the state of dilute solution. On the one hand, it can reduce the drying process of HPA-GO and maintain its dispersibility; on the other hand, the fluidity of the dilute solution of BMI resin is very good, and HPA-GO and BMI resin can fully collide, contact and react under stirring and dispersion. Part of BMI resin reacts with GO in advance and wraps on its surface to form a spherical shell structure, which reduces the contact and agglomeration between the sheets and avoids the agglomeration of HPA-GO in the subsequent viscous concentrated solution. Ball milling can also better disperse the nanoparticles.

[0024] (3) By using solvent replacement and extraction, the modified resin is precipitated from the solvent using a poor solvent with a low boiling point, and then the poor solvent is evaporated at a relatively low temperature. The heating temperature and heating time are greatly reduced, thereby solving the problem of difficult and incomplete removal of DMF, and achieving convenient, rapid, efficient, and large-scale extraction of the resin;

[0025] (4) All amino-containing substances used in the modification methods in the prior art are small molecular substances. The present application uses high molecular weight polymer materials. Unlike small molecular substances, the purpose of modification is only to connect the resin and graphene oxide. Instead, it relies on the long chain structure of the macromolecule to toughen, reduce the cross-linking density of the resin, and construct a hyperbranched structure.

[0026] (5) The present application mixes graphene oxide and resin in a solution, and achieves uniform dispersion of graphene oxide in the resin by ball milling. The graphene oxide can react at a relatively low temperature without heating the resin to melt before reacting. The solution blending process is superior to the melt blending process in terms of dispersibility, thereby obtaining a hyperbranched polyamide functionalized graphene oxide (HPA-GO) modified bismaleimide (BMI) resin having excellent flexural strength, modulus and glass transition temperature properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The modified graphene oxide prepared in Example 1 was subjected to Fourier transform infrared spectroscopy (FT-IR spectroscopy) analysis and X-ray photoelectron spectroscopy (XPS spectroscopy) analysis;

[0028] Figure 2 Conducting GPC molecular weight test for the modified graphene oxide prepared in Example 1;

[0029] Figure 3 The modified graphene oxide prepared in Example 1 was subjected to spectral analysis test. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] In addition, in the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes, and do not specifically refer to the order or sequence, nor are they used to limit the present invention. They are only used to distinguish components or operations described with the same technical terms, and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions and technical features between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0032] Unless otherwise specified, the examples and comparative examples are parallel tests with the same components, component contents, preparation steps and preparation parameters. The experimental methods in the following examples are conventional methods unless otherwise specified. The test materials used in the following examples are analytical reagents (AR) unless otherwise specified. Parts are parts by weight unless otherwise specified, and the materials are purchased from commercial channels.

[0033] Graphene oxide GO was purchased from Hangzhou Gaoxin Technology Co., Ltd., with an average flake size of 5-8 μm and an average flake layer monolayer rate of >99.5%; ethylenetriamine, methyl acrylate, ethylenediamine, diphenylbismaleimide, diallyl bisphenol A, deionized water and DMF were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0034] Example 1

[0035] (1) Add diethylenetriamine and methyl acrylate in a molar ratio of 1:1 into a three-necked flask, react for 20 hours under a nitrogen atmosphere at -10-20°C, then add ethylenediamine, the molar ratio of diethylenetriamine, methyl acrylate and ethylenediamine is 6:6:1, react at 100°C for 10 hours to obtain HPA.

[0036] (2) 30 parts of GO, 40 parts of DMF and 30 parts of HPA were added into a three-necked flask, reacted at 100°C for 30 h, washed and centrifuged to obtain HPA-GO.

[0037] (3) Add 30 parts of diphenylbismaleimide and 30 parts of DMF solution into a flask, ultrasonicate until the resin is dissolved, add HPA-GO at a weight ratio of 0.01 to BMI resin at 50°C, stir at 4000 r / min for 1.5 h to react the amine group with the double bond of BMI resin, add 80 parts of diphenylbismaleimide, stir at 6000 r / min for 1.5 h, and premix to obtain a premixed solution.

[0038] (4) Pour the premixed solution obtained in (3) into the tank of a ball mill and mix at a rotation speed of 500 r / min for 6 h.

[0039] (5) The uniformly mixed solution obtained in (4) was poured into 500 parts of deionized water to precipitate the resin, and the uniformly mixed resin powder was obtained by washing and filtering, and then dried at 100°C.

[0040] (6) Add 200 parts of diallyl bisphenol A to the above resin powder at 120° C. Prepolymerize with mechanical stirring at a speed of 2000 r / min for 1.5 hours to obtain a prepolymer.

[0041] (7) The prepolymer described in (6) is subjected to a degassing treatment in a vacuum oven at 150° C. and then step-cured in an oven to obtain an HPA-GO modified BMI resin.

[0042] Example 2

[0043] (1) Add diethylenetriamine and methyl acrylate in a molar ratio of 1:1 into a three-necked flask, react for 10 hours under a nitrogen atmosphere at -10-20°C, then add ethylenediamine, the molar ratio of diethylenetriamine, methyl acrylate and ethylenediamine being 2:2:1, and react at 70°C for 5 hours to obtain HPA.

[0044] (2) 10 parts of GO, 10 parts of DMF, and 10 parts of HPA were added into a three-necked flask, reacted at 100°C for 30 h, washed and centrifuged to obtain HPA-GO.

[0045] (3) Add 10 parts of diphenylbismaleimide and 20 parts of DMF solution into a flask, ultrasonicate until the resin is dissolved, add HPA-GO at a weight ratio of 0.001 to BMI resin at 50°C, stir at a speed of 1000 r / min for 1 hour to react the amine group with the double bond of the BMI resin, add 90 parts of diphenylbismaleimide, stir at a speed of 1000 r / min for 1 hour, and premix to obtain a premixed solution.

[0046] (4) Pour the premixed solution obtained in (3) into the tank of a ball mill and mix at a speed of 200 r / min for 2 h.

[0047] (5) The uniformly mixed solution obtained in (4) was poured into 200 parts of deionized water to precipitate the resin, and the uniformly mixed resin powder was obtained by washing and filtering, and then dried at 80°C.

[0048] (6) Add 50 parts of diallyl bisphenol A to the above resin powder at 110° C. Prepolymerize with mechanical stirring at a speed of 1000 r / min for 1 hour to obtain a prepolymer.

[0049] (7) The prepolymer described in (6) is subjected to a degassing treatment in a vacuum oven at 120° C. and then step-cured in an oven to obtain an HPA-GO modified BMI resin.

[0050] Example 3

[0051] (1) Add diethylenetriamine and methyl acrylate in a molar ratio of 1:1 into a three-necked flask, react for 20 hours under a nitrogen atmosphere at -10-20°C, then add ethylenediamine, the molar ratio of diethylenetriamine, methyl acrylate and ethylenediamine being 14:14:1, and react for 10 hours at 130°C to obtain HPA.

[0052] (2) 40 parts of GO, 40 parts of N,N-dimethylformamide DMF, and 40 parts of HPA were added to a three-necked flask, reacted at 110°C for 30 hours, washed and centrifuged to obtain HPA-GO.

[0053] (3) Add 20 parts of diphenyl bismaleimide and 40 parts of DMF solution into a flask, ultrasonicate until the resin is dissolved, add HPA-GO at a weight ratio of 0.0008 to BMI resin at 50°C, stir at 7000 r / min for 2 h to react the amine group with the double bond of the BMI resin, add 120 parts of diphenyl bismaleimide, stir at 8000 r / min for 2 h, and premix to obtain a premixed solution.

[0054] (4) Pour the premixed solution obtained in (3) into the tank of a ball mill and mix at a rotation speed of 700 r / min for 6 h.

[0055] (5) The uniform mixed solution obtained in (4) was poured into 700 parts of deionized water to precipitate the resin, and the uniformly mixed resin powder was obtained by washing and filtering, and then dried at 110°C.

[0056] (6) Add 210 parts of diallyl bisphenol A to the above resin powder at 130° C. Prepolymerize with mechanical stirring at a speed of 2500 r / min for 2 hours to obtain a prepolymer.

[0057] (7) The prepolymer described in (6) is subjected to a degassing treatment in a vacuum oven at 150° C. and then step-cured in an oven to obtain an HPA-GO modified BMI resin.

[0058] Example 4

[0059] (1) Add diethylenetriamine and methyl acrylate in a molar ratio of 1:1 into a three-necked flask, react for 20 hours under a nitrogen atmosphere at -10-20°C, then add ethylenediamine, the molar ratio of diethylenetriamine, methyl acrylate and ethylenediamine being 30:30:1, and react for 12 hours at 140°C to obtain HPA.

[0060] (2) 50 parts of GO, 50 parts of DMF, and 50 parts of HPA were added to a three-necked flask, reacted at 120°C for 36 hours, washed and centrifuged to obtain HPA-GO.

[0061] (3) Add 10 parts of diphenylbismaleimide and 50 parts of DMF solution into a flask, ultrasonicate until the resin is dissolved, add HPA-GO at a weight ratio of 0.009 to BMI resin at 50°C, stir at 8000 r / min for 2 h to react the amine group with the double bond of the BMI resin, add 140 parts of diphenylbismaleimide, stir at 8000 r / min for 2 h, and premix to obtain a premixed solution.

[0062] (4) Pour the premixed solution obtained in (3) into the tank of a ball mill and mix at a rotation speed of 800 r / min for 8 h.

[0063] (5) The uniformly mixed solution obtained in (4) was poured into 800 parts of deionized water to precipitate the resin, and the uniformly mixed resin powder was obtained by washing and filtering, and then dried at 120°C.

[0064] (6) Add 225 parts of diallyl bisphenol A to the above resin powder at 130° C. Prepolymerize with mechanical stirring at a speed of 3000 r / min for 2 hours to obtain a prepolymer.

[0065] (7) The prepolymer described in (6) is subjected to a degassing treatment in a vacuum oven at 160° C. and then step-cured in an oven to obtain an HPA-GO modified BMI resin.

[0066] Comparative Example 1

[0067] The difference from Example 1 is that in step (3), an equal weight portion of HPA-GO is missing, and the rest is the same as Example 1.

[0068] Comparative Example 2

[0069] The difference from Example 1 is that in step (2), an equal weight portion of HPA is missing, and the rest is the same as Example 1.

[0070] Comparative Example 3

[0071] The difference from Example 1 is that an equal weight portion of GO is missing in step (2), and the rest is consistent with Example 1.

[0072] Performance Testing

[0073] 1. Infrared and X-ray testing:

[0074] The modified graphene oxide prepared in Example 1 was analyzed by Fourier transform infrared spectroscopy (FT-IR spectroscopy) and X-ray photoelectron spectroscopy (XPS spectroscopy) to obtain the modification of GO. The FT-IR spectrum uses Frontier FTIR to characterize the changes in the infrared characteristic peaks of GO before and after the reaction. The FT-IR sample is prepared by the KBr tablet method, and the test range is 400-4000cm -1 The XPS spectrum uses ESCALABXi+ to characterize the element changes of GO before and after the reaction and the chemical state of the elements therein.

[0075] from Figure 1 In the FT-IR spectrum, it can be seen that 1557cm -1 The absorption peak of CN appears at , and the N content on the GO surface in the XPS spectrum increases significantly, and the carbon-oxygen ratio increases. This is due to the successful grafting of HPA onto the GO surface, which achieves amino modification on the GO surface.

[0076] 2. Flexural strength, modulus and glass transition temperature test

[0077] The bending strength, modulus and glass transition temperature of the embodiment and the comparative example were tested. The bending strength and modulus were tested according to GB / T2567-2021, using a three-point bending load test, the testing instrument was INSTRON 5966 electronic universal material testing machine, the test temperature was 25°C, the humidity was 47%, and the glass transition temperature testing instrument was DMA242 E. The test method was: ASTMD7028-07 (2015), three-point bending mode, heating range RT-350°C, heating rate 5K / min, frequency 1Hz, and the results are shown in Table 1.

[0078] Table 1

[0079]

[0080]

[0081] It can be seen from Table 1 that the performance of Example 1 is significantly improved compared with the unmodified resin and the resin with only GO or HPA added, indicating that the addition of HPA-GO can significantly improve the flexural strength of the resin and slightly increase the flexural modulus and glass transition temperature.

[0082] 3. GPC molecular weight and spectral analysis test

[0083] GPC molecular weight test was performed on Example 1, and the results are shown in Figure 2 ,from Figure 2 It can be seen that the weight average molecular weight is 2708 g / mol and the number average molecular weight is 2600 g / mol. It can be proved that the synthesized substance is a high molecular weight substance, namely, hyperbranched polyamide functionalized graphene oxide (HPA-GO) modified bismaleimide (BMI) resin.

[0084] The spectrum analysis test of Example 1 is shown in Figure 3 ,from Figure 3 It can be seen that 3283cm -1 Corresponding to -NH; 2929cm -1 Corresponding to -CH; 1651cm -1 Corresponding to -C=O; 1456cm -1 Corresponding to -CN, it is consistent with the molecular structure of hyperbranched polyamide.

[0085] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. Hyperbranched polyamide functionalized graphene oxide modified bismaleimide resin, the preparation raw materials include the following components: DMF dispersion of HPA-GO, diphenyl bismaleimide, deionized water and diallyl bisphenol A.

2. The HPA-GO modified BMI resin according to claim 1, characterized in that The raw materials for preparing the HPA-GO modified BMI resin include the following components by weight: 20-50 parts of DMF dispersion of HPA-GO, 100-150 parts of diphenyl bismaleimide, 200-800 parts of deionized water and 50-225 parts of diallyl bisphenol A.

3. The HPA-GO modified BMI resin according to claim 1 or 2, characterized in that The raw materials for preparing the DMF dispersion of HPA-GO include the following components by weight: 10-20 parts of graphene oxide dispersion, 100-200 parts of DMF and 1-5 parts of HPA.

4. The HPA-GO modified BMI resin according to any one of claims 1 to 3, characterized in that: The preparation method of the DMF dispersion of HPA-GO comprises: reacting GO, DMF and HPA, washing and centrifuging to obtain HPA-GO; Preferably, the reaction temperature of GO, DMF and HPA is 80-120° C., and the reaction time is 12-36 h.

5. The HPA-GO modified BMI resin according to claim 4, characterized in that The preparation method of the HPA-GO modified BMI comprises: adding diethylenetriamine and methyl acrylate, reacting under a nitrogen atmosphere, and adding ethylenediamine to react to obtain a hyperbranched polyamide.

6. The HPA-GO modified BMI resin according to claim 5, characterized in that The molar ratio of the added diethylenetriamine and methyl acrylate is 1:

1.

7. The HPA-GO modified BMI resin according to claim 5, characterized in that The molar ratio of the added diethylenetriamine and ethylenediamine is (2-30):

1.

8. The HPA-GO modified BMI resin according to claim 5, characterized in that The reaction temperature under nitrogen atmosphere is -10-20°C, the reaction time is 10-24h, and the reaction temperature after adding ethylenediamine is 70-140°C, the reaction time is 5-12h.

9. The HPA-GO modified BMI resin according to claim 1, characterized in that Add 10-50 parts of the DMF dispersion of diphenyl bismaleimide and 20-50 parts of HPA-GO, dissolve by ultrasonication, add HPA-GO at a weight ratio of 0.0001-0.01 to BMI resin at 50°C, stir at a speed of 1000-8000 r / min for 1-2h, add 90-100 parts of diphenyl bismaleimide and stir to obtain a premixed solution, pour the obtained premixed solution into the tank of a ball mill, and grind at 200 -800r / min for 2-8h to obtain a uniform mixed solution, pour the obtained uniform mixed solution into 200-800 parts of deionized water to precipitate the resin, wash and filter to obtain resin powder, and dry it at 80-120°C; add 50-225 parts of diallyl bisphenol A to the resin powder at 110-140°C, and prepolymerize it for 1-2h with mechanical stirring at a speed of 1000-3000r / min to obtain a prepolymer.

10. The HPA-GO modified BMI resin according to claim 9, characterized in that The prepolymer is subjected to a degassing treatment in a vacuum oven at 120-160° C. and then step-cured in an oven to obtain a HPA-GO modified BMI resin.